Evaluación in vitro de la actividad antibacteriana y antimicótica de los extractos de dos especies de plantas del género amaranthus aplicado sobre cepas de interés clínico en el periodo diciembre de 2013 – mayo de 2014 - Garcia Silva, Diana Carolina (2015)
This work is done in the Research Laboratory of the Faculty of Health Sciences of the National University of Chimborazo, in order to determine the antibacterial and antifungal activity of lipid extracts, ethanolic and flavonoids amaranth and Sangorache. It consists of a description of the problem to investigate with clear objectives which are the purposes of research work as well as a theoretical framework that will help the compression of the subject under study. the technique of disk diffusion (Kirby-Bauer) was used. standardized concentrations ATCC strains of microorganisms of clinical interest as were used: Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 9637, Klebsiella pneumoniae ATCC 10031, Micrococcus flavus ATCC 14452, Candida albicans Saccharomyces cerevisiae ATCC 10231 ATCC 2601. and different amounts of were impregnated extracts discs to test the antimicrobial susceptibility. bacterial and fungal concentration from 0.5 McFarland (MCF), on a surface of Mueller Hinton agar (for bacteria) and Sabouraud (for fungi) strains inoculum, and were distributed evenly, allowed stand for a period of 5 min and preparations discs being placed incubation at 37 ° C for a period of 18 hours. As a positive control of antibacterial activity discs streptomycin (10 and 300 ug) it was used, and for antifungal activity capsules fluconazole (150 mg) was used also extracts natural plant such as Eucalyptus was used in volumes of 20 uL 100%.